Novel titin-inspired high-performance polyurethanes with self-healing and recyclable capacities based on dual dynamic network. (16th September 2021) - Xie, Haopu; Liu, Xiangdong; Sheng, Dekun; Wu, Haohao; Zhou, Yan; Tian, Xinxin; Sun, Yinglu; Shi, Biru; Yang, Yuming
Abstract: It is still a huge challenge that integrating excellent mechanical performance and high healing efficiency into self-healing materials at the same time, even if numerous dynamic bonds have been explored in preparing of self-healing materials in the last 20 years. Herein, we reported a novel titin-inspired strategy to prepare the polyurethanes via introducing dual dynamic network which contained the physical cross-linking of quadruple hydrogen bonds formed by 5-(2-hydroxyethyl)-6-methyl-2-aminouracil (UPy) dimers and the covalent cross-linking of Diels-Alder (D-A) bonds. Specially, relying on the synergistic effect of the dual dynamic network, the resulting polyurethane F50 U50 -PU exhibited admirable mechanical performance, such as a super-high strength of 51.9 MPa, a superb toughness of 166.7 MJ/m 3 and a large elongation at break of 930%. Meanwhile, on account of the dynamic feature of quadruple hydrogen bonds and D-A bonds, the resulting polyurethane showed a high heat-induced healing efficiency of 91.2%. More importantly, the polyurethanes could be recycled by hot-pressing process to regain their initial mechanical properties and integrity. And it was also used as substrate to construct self-healing conductive device, which displayed splendid self-healing of electrical conductivity after damage. It can be envisioned that the polyurethanes with both superior mechanical performance and high healing efficiencies have great application prospect in multifarious fields. Graphical abstract: Image 1 Highlights: Novel titin-inspired self-healing polyurethanes with dual dynamic network were prepared. The optimal sample F50 U50 -PU showed a super-high strength of 51.9 MPa with a healing efficiency of 91.2%. The materials can be recycled by cutting/hot-pressing process. A self-healing conductive device with self-healing ability was explored.